Systematic hybrid laparoscopic and endovascular treatment of median arcuate ligament syndrome: A single-center experience - Schneider, Michael; Longchamp, Justine; Uldry, Emilie; Corpataux, Jean-Marc; Kefleyesus, Amaniel; Halkic, Nermin (Frontiers in Surgery, 2023)
Background: Median arcuate ligament syndrome (MALS) is caused by coeliac trunk (CT) compression by the median arcuate ligament. Clinically, this pathology varies from post-prandial pain (Dunbar syndrome) to a life-threatening haemorrhage due to rupture of a gastroduodenal artery aneurysm (GAA). Due to the low prevalence of this disease, there is no standard management of the MALS. Material and Method: This was a single-center, retrospective study of 13 patients. Two groups were identified based on the initial clinical presentation: those operated for a GAA rupture (bleeding group – BG) and those operated electively for Dunbar syndrome (Dunbar syndrome group – DG). The primary endpoint was 30-day post-operative complications of a systematic laparoscopic release of median arcuate ligament and stenting during the same procedure. Results: Seven patients (54%) underwent elective surgery. Six patients (46%) had semi-urgent repair under elective conditions post embolization for GAA bleeding. Total operative time was longer in the BG (p=0.06). Two patients in the BG had early major complications and needed reintervention with a comprehensive complication index lower in the DG. There was no mortality at 30 days. Overall median length of stay was 5 days (IQR 3.5-15.3). Patients in the DG had a significantly shorter length of stay (p=0.02). At 6 months, primary and secondary CT stent patencies were 82% and 100%, respectively. There were no high flow GAA recurrencies. Conclusions: A combined approach of laparoscopic release of median arcuate ligament and stenting during the same procedure is feasible and safe and this approach must be systematically discussed in symptomatic patients.